Low-threshold collinear parametric Raman comb generation in calcite under 532 and 1064 nm picosecond laser pumping. (25th August 2015) - Smetanin, S N; Jelínek, M; Kubeček, V; Jelínková, H
Abstract: Optimal conditions of low-threshold collinear parametric Raman comb generation in calcite (CaCO3 ) are experimentally investigated under 20 ps laser pulse excitation, in agreement with the theoretical study. The collinear parametric Raman generation of the highest number of Raman components in the short calcite crystals corresponding to the optimal condition of Stokes–anti-Stokes coupling was achieved. At the excitation wavelength of 1064 nm, using the optimum-length crystal resulted in the effective multi-octave frequency Raman comb generation containing up to five anti-Stokes and more than four Stokes components (from 674 nm to 1978 nm). The 532 nm pumping resulted in the frequency Raman comb generation from the 477 nm 2nd anti-Stokes up to the 692 nm 4th Stokes component. Using the crystal with a non-optimal length leads to the Stokes components generation only with higher thresholds because of the cascade-like stimulated Raman scattering with suppressed parametric coupling.